Serendipitous discovery of a tidal tail in NGC632 - PATAT, FERDINANDO; CARRARO, GIOVANNI; ROMANIELLO, MARTINO (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2002)
While searching for a light echo of the Ia SN1998es type in NGC632, we discovered a very faint tidal tail, which extends for at least 50 kpc from the galaxy nucleus. This finding, together with the presence of a strong nuclear starburst, the boxy shape of the isophotes and their twisting, strongly suggests that what we see in NGC632 is the result of a galaxy merger. NGC632 was previously classified as an S0, while the deep VLT imaging discussed in this paper shows very clearly the presence of spiral arms, on top of which rather blue knots appear to be projected. They are possible sites of star formation, probably triggered by the galaxy merger. Further observations needed to clarify the open questions are outlined.